Serine suppresses the motor function of a periplasmic PomB mutation in the Vibrio flagella stator. (23rd March 2016) - Nishikino, Tatsuro; Zhu, Shiwei; Takekawa, Norihiro; Kojima, Seiji; Onoue, Yasuhiro; Homma, Michio
Abstract : The flagellar motor of Vibrio alginolyticus is made of two parts: a stator consisting of proteins PomA and PomB, and a rotor whose main component is FliG. The interaction between FliG and PomA generates torque for flagellar rotation. Based on cross‐linking experiments of double‐Cys mutants of PomB, we previously proposed that a conformational change in the periplasmic region of PomB caused stator activation. Double‐Cys mutants lost their motility due to an intramolecular disulfide bridge. In this study, we found that the addition of serine, a chemotactic attractant, to a PomB(L160C/I186C) mutant restored motility without cleaving the disulfide bridge. We speculate that serine changed the rotor (FliG) conformation, affecting rotational direction. Combined with the counterclockwise (CCW)‐biased mutation FliG(G214S), motility of PomB(L160C/I186C) was restored without the addition of serine. Likewise, motility was restored without serine in Che − mutants, in either a CCW‐locked or clockwise (CW)‐locked strain. In contrast, in a Δ cheY (CCW‐locked) strain, Vibrio (L160C/I186C) required serine to be rescued. We speculate that CheY affects stator conformation and motility restoration by serine is independent on the chemotaxis signaling pathway. Abstract : We found that the addition of serine, a chemotactic attractant, to a PomB(L160C/I186C) mutant restored motility without cleaving the disulfide bridge in Vibrio. Motility was restored without serine in Che − mutants. We speculate that serine changed the rotor conformation to suppress the motor function of the PomB mutation.